2017
DOI: 10.1103/physrevb.96.235433
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-induced interface states in a topological-insulator–ferromagnetic-metal heterostructure

Abstract: Recent experiments demonstrating large spin-transfer torques in topological insulator (TI)-ferromagnetic metal (FM) bilayers have generated a great deal of excitement due to their potential applications in spintronics. The source of the observed spin-transfer torque, however, remains unclear. This is because the large charge transfer from the FM to TI layer would prevent the Dirac cone at the interface from being anywhere near the Fermi level to contribute to the observed spintransfer torque. Moreover, there i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
(51 reference statements)
3
18
0
Order By: Relevance
“…3 (D and E) and 4A represent the first unambiguous demonstration of TSS-driven magnetization switching. As mentioned above, the SOT switching in recent studies on TI/FM systems ( 6 12 ) may not be TSS-driven because interfacing a TI layer with a conductive FM film can significantly modify or even completely suppress the TSSs in the TI layer ( 14 18 ). In contrast, the BaFe 12 O 19 layer in this work is an MI, which is expected to produce negligible effects on the TSSs ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 (D and E) and 4A represent the first unambiguous demonstration of TSS-driven magnetization switching. As mentioned above, the SOT switching in recent studies on TI/FM systems ( 6 12 ) may not be TSS-driven because interfacing a TI layer with a conductive FM film can significantly modify or even completely suppress the TSSs in the TI layer ( 14 18 ). In contrast, the BaFe 12 O 19 layer in this work is an MI, which is expected to produce negligible effects on the TSSs ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…2(a)-2(f) with Fig. 1(b) [40,41]. For thin films (<5 QLs) we also observe an energy gap in the vicinity of the two Dirac points which decreases with increasing TI overlayer thickness.…”
Section: Resultsmentioning
confidence: 55%
“…[ 42–45 ] 2)Previous work has shown that interfacing a TI with a ferromagnet can damage or suppress the TSS in the TI. [ 10,35–38 ] The comparison between the damping of the InSb/α‐Sn/Ag/NiFe and InSb/α‐Sn/NiFe samples in Figure 4 evidently suggests that this is also the case for the TSS in the TDS α‐Sn. 3)TDSs should also host Fermi arc surface states; [ 46,47 ] in the case of TDS α‐Sn, such states are expected to exist on surfaces parallel to the uniaxial tensile axis, [ 16 ] namely, the four side surfaces of the α‐Sn film in this work. Future studies on spin pumping effects associated with these surface states are very interesting. 4)This work suggests that SOC in the bulk of α‐Sn and β‐Sn films is no stronger than that in Ag.…”
Section: Resultsmentioning
confidence: 83%
“…[ 10 ] Previous experimental and theoretical works have shown that the magnetism in a ferromagnetic metal can significantly modify and even completely suppress TSS in a neighboring TI or α‐Sn thin film. [ 10,35–38 ]…”
Section: Resultsmentioning
confidence: 99%